Bifurcation of Cell Migratory and Proliferative Signaling by the Adaptor Protein Shc - Collins, Lila R. (The Rockefeller University Press, 1999)
Cytokines and extracellular matrix proteins initiate signaling cascades that regulate cell migration and proliferation. Evidence is provided that the adaptor protein Shc can differentially regulate these processes. Specifically, under growth factor–limiting conditions, Shc stimulates haptotactic cell migration without affecting anchorage-dependent proliferation. However, when growth factors are present, Shc no longer influences cell migration; rather, Shc is crucial for DNA synthesis. Mutational analysis of Shc demonstrates that, while tyrosine phosphorylation is required for both DNA synthesis and cell migration, the switch in Shc signaling is associated with differential use of Shc's phosphotyrosine interacting domains; the PTB domain regulates haptotaxis, while the SH2 domain is selectively required for proliferation.